Nursing students’ grit: a cross-sectional study - Kang, Se-Won (Advances in Social Sciences Research Journal, 2018)
This descriptive study aimed to investigate the grit of nursing students. Participants were 273 students from two nursing departments in South Korea. Data were collected from March to August 2018. Data were analysed using mean, standard deviation, the independent samples t-test, and analysis of variance (ANOVA), using the IBM SPSS Statistics 22.0 program. The grit score of the nursing students was 3.27 (out of 5), and those on the sub-factors consistency interest and perseverance of effort were 3.13 and 3.40 out of 5, respectively. Grit scores differed significantly according to gender. Males tended to show higher scores than females on grit (t=4.684, p<0.001) and on the sub-factors consistency interest and perseverance of effort (t=3.922, p<0.001; t=3.978, p<0.001, respectively). It is therefore necessary to find ways to increase the grit of female students. Research on grit in college students needs to continue.